Developing a checklist for evaluating the presentation of new vocabulary in ELT textbooks - Mat Hussin, Nur Izyan Syamimi; Nimehchisalem, Vahid; Kalajahi, Seyed Ali Rezvani (Penerbit Universiti Malaysia Pahang, 2015)
Textbook evaluation can be a guide and reference to the educational institutions, curriculum designers, writers and educators in selecting the suitable material regarding their learners’ needs. A checklist is one of the common instruments used in textbook evaluation studies. Many checklists have been developed to evaluate whole textbooks. However, few checklists are available that focus on a specific feature of an English language learning-teaching textbook. This study presents the development procedure of a checklist that focuses on the presentation of vocabulary in ELT textbooks. The instrument was developed in the light of a number of previous evaluation checklists. It was further refined based on interviews with a number of English language teachers, who commented on the relevance and clarity of its items. The reliability test revealed very high overall internal reliability of the instrument. The paper presents the checklist that can be used as a guide and reference to other researchers, curriculum designers, writers, teachers, as well as material evaluators.